2013
DOI: 10.1186/1471-2105-14-325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of single nucleotide polymorphisms from the transcriptome of an organism with a whole genome duplication

Abstract: BackgroundThe common ancestor of salmonid fishes, including rainbow trout (Oncorhynchus mykiss), experienced a whole genome duplication between 20 and 100 million years ago, and many of the duplicated genes have been retained in the trout genome. This retention complicates efforts to detect allelic variation in salmonid fishes. Specifically, single nucleotide polymorphism (SNP) detection is problematic because nucleotide variation can be found between the duplicate copies (paralogs) of a gene as well as betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Several genomic resources have been developed for research to help improve rainbow trout commercial production traits including disease resistance. The list includes clonal lines (Young et al, 1996 ; Thorgaard et al, 2002 ), BAC libraries (Palti et al, 2004 ), genetic linkage maps (Young et al, 1998 ; Sakamoto et al, 2000 ; Rexroad et al, 2008 ; Palti et al, 2011 ; Guyomard et al, 2012 ), microarrays (Salem et al, 2008 ), expressed sequence tags (ESTs) (Rexroad et al, 2003 ; Sánchez et al, 2009 ; Boussaha et al, 2012 ), single nucleotide polymorphisms (SNPs) (Sánchez et al, 2009 ; Amish et al, 2012 ; Boussaha et al, 2012 ; Houston et al, 2012 ; Salem et al, 2012 ; Christensen et al, 2013 ; Colussi et al, 2014 ; Palti et al, 2014 ), next-generation sequence read archives (SRA) and genome as well as transcriptome reference assemblies (Salem et al, 2010 ; Sanchez et al, 2011 ; Berthelot et al, 2014 ; Fox et al, 2014 ). Several studies have identified many immune-related key genes and gene networks (Thorgaard et al, 2002 ; Cerdà et al, 2008 ; Chiu et al, 2010 ; Zhang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several genomic resources have been developed for research to help improve rainbow trout commercial production traits including disease resistance. The list includes clonal lines (Young et al, 1996 ; Thorgaard et al, 2002 ), BAC libraries (Palti et al, 2004 ), genetic linkage maps (Young et al, 1998 ; Sakamoto et al, 2000 ; Rexroad et al, 2008 ; Palti et al, 2011 ; Guyomard et al, 2012 ), microarrays (Salem et al, 2008 ), expressed sequence tags (ESTs) (Rexroad et al, 2003 ; Sánchez et al, 2009 ; Boussaha et al, 2012 ), single nucleotide polymorphisms (SNPs) (Sánchez et al, 2009 ; Amish et al, 2012 ; Boussaha et al, 2012 ; Houston et al, 2012 ; Salem et al, 2012 ; Christensen et al, 2013 ; Colussi et al, 2014 ; Palti et al, 2014 ), next-generation sequence read archives (SRA) and genome as well as transcriptome reference assemblies (Salem et al, 2010 ; Sanchez et al, 2011 ; Berthelot et al, 2014 ; Fox et al, 2014 ). Several studies have identified many immune-related key genes and gene networks (Thorgaard et al, 2002 ; Cerdà et al, 2008 ; Chiu et al, 2010 ; Zhang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This problem has been efficiently addressed with a “filter” that used haploid genomic information because there should be no heterozygotes (Christensen et al . ; Larson et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…These paralogs appeared to be a major problem here given the low conversion of sequence variants into functional assays in nuclear-encoded subunits of the mitochondrial machinery. This problem has been efficiently addressed with a "filter" that used haploid genomic information because there should be no heterozygotes (Christensen et al 2013;Larson et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) have begun to replace microsatellites in many studies of relatedness and parentage because they are easier to score and becoming cheaper to develop (Morin, Luikart, & Wayne, ; Städele & Vigilant, ; Vignal, Milan, SanCristobal, & Eggen, ; Weinman, Solomon, & Rubenstein, ). However, in species with complicated genomes characterized by extensive gene duplication (including polyploidy), the presence of paralogs makes identifying SNPs challenging (Christensen et al., ; Dufresne, Stift, Vergilino, & Mable, ). In contrast, identifying polysomic microsatellite markers is easier because multiple alleles can be determined visually in genotyping output (David, Blum, Feldman, Lavi, & Hillel, ; Huang, Cipriani, Morgante, & Testolin, ).…”
Section: Introductionmentioning
confidence: 99%